PROSES PENGAMBILAN KEPUTUSAN MENJADI ISTERI KEDUA DALAM PERKAWINAN POLIGAMI PADA WANITA BERPENDIDIKAN TINGGI - Irfan Fahmi (Psympathic : Jurnal Ilmiah Psikologi, 2014)
This study focused on the decision-making process became the second wife in a polygamous marriage by highly-educated women along with the factors that influence it. This study is a qualitative approach with subjects were 3 women aged 30-55 years old with minimum education level was undergraduate and serves as a second wife. From the interviews analysis, it concluded that the decision-making process undertaken by subjects were very diverse and complicated. All subjects through every stage of the decision making process vary depending on the obstacles and problems that they faced. The main factors that affect the subjects in the decision became the second wife is a factor of circumstances, in particular subjects who came from descended polygamy marriage and belief factor, that being the second wife is the providence of God that must be accepted. Suggestions for further research are expected to perform data retrieval from significant others who know the decision-making process taken by the subject